Development and Validation of the Win-Win Scale - Zhang, Shan; Zang, Xinlei; Zhang, Feng (Frontiers in Psychology, 2021)
Accumulating evidence has shown that win-win is necessary for both individuals and society. This research, including two studies, aims to develop a measurement tool to evaluate win-win effectively. Our pilot study developed the item pool containing 49 items involved in the five dimensions and 29 feature words. In the first study, we screened the items by item analysis, extracted common factors using exploratory factor analysis (EFA), and determined a total of 25 items in the initial scale. In the second study, we used the first and second-order confirmatory factor analysis (CFA) to test the scale's construct validity. The results showed that the structural equation model reliably fit the index up to the standard. Based on our results, we have formed a win-win scale by retaining 16 items from the original project pool.